Development and RF-Performance of AlGaN/GaN and InAlN/GaN HEMTs on Large-Diameter High-Resistivity Silicon Substrates - Moser, M.; Pradhan, M.; Alomari, M.; Schoch, B.; Sharma, K.; Kallfass, I.; García-Luque, A.; Martín-Guerrero, Teresa María; Burghartz, J. N. (My University, 2022)
A CMOS-compatible industrial processing and RF analysis of 150 mm GaN-on-HR-Si substrates with AlGaN and InAlN barrier is presented. Process development along with transfer to large-wafer scale is shown and some HEMT calibration devices produced on AlGaN/GaN following the aforementioned procedure are characterized in terms of RF-performance by using a set of measured multi-bias S-parameters. An automatic small-signal equivalent circuit extraction strategy for these AlGaN/GaN DUTs is validated and some de-embedded figures of merit are drawn out in order to initially evaluate this promising technology.
Keywords: Silicio; Aluminio; Aluminium Gallium Nitride (AlGaN); Indium Aluminium Nitride (InAlN); High Resistivity Silicon (HR-Si); High-Electron Mobility Transistor (HEMT)